Gymnosporia thyrsiflora comb. nov. (Celastraceae), a correct name to replace G. graciliramula from southwest China. (6th December 2013) - Yu, Wen‐Bin; Wang, Hong; Li, De‐Zhu
<x xml:space="preserve">Abstract</x> In 'Flora of China', the combination 'Gymnosporia graciliramula (S. J. Pei & Y. H. Li) Q. R. Liu & Funston' was proposed, but this name was not validly published in 2008 because the presumed basionym Maytenus graciliramula S. J. Pei & Y. H. Li was not published in 1979 as stated, but in 1981, contrary to Article 33.4 of ICBN. Meanwhile, two older names, M. thyrsiflora S. J. Pei & Y. H. Li and M. pseudoracemosa S. J. Pei & Y. H. Li, were listed as synonyms in conflict with article 52.3 of ICBN. In this article, we propose a new combination G. thyrsiflora (S. J. Pei & Y. H. Li) W. B. Yu & D. Z. Li that is the correct name when G. thyrsiflora, M. pseudoracemosa and M. graciliramula are treated as a single species in Gymnosporia.